Outcomes of vascular resection associated with curative intent hepatectomy for intrahepatic cholangiocarcinoma. Issue 9 (September 2020) - Conci, Simone; Viganò, Luca; Ercolani, Giorgio; Gonzalez, Esteban; Ruzzenente, Andrea; Isa, Giulia; Salaris, Claudia; Fontana, Andrea; Bagante, Fabio; Pedrazzani, Corrado; Campagnaro, Tommaso; Iacono, Calogero; et al.
Abstract: Background and aims: We aimed to investigate the impact of vascular resection (VR) on postoperative outcomes and survival of patients undergoing hepatectomy for intrahepatic cholangiocarcinoma (ICC). Methods: A retrospective analysis of a multi-institutional series of 270 patients with resected ICC was carried out. Patients were divided into three groups: portal vein VR (PVR), inferior vena cava VR (CVR) and no VR (NVR). Univariate and multivariate analysis were applied to define the impact of VR on postoperative outcomes and survival. Results: Thirty-one patients (11.5%) underwent VR: 15 (5.6%) to PVR and 16 (5.9%) to CVR. R0 resection rates were 73.6% in NVR, 73.3% of PVR and 68.8% in CVR. The postoperative mortality rate was increased in VR groups: 2.5% in NVR, 6.7% in PVR and 12.5% in CVR. The 5-years overall survival (OS) rates progressively decreased from 38.4% in NVR, to 30.1% in CVR and to 22.2% in PVR, p = 0.030. However, multivariable analysis did not confirm an association between VR and prognosis. The following prognostic factors were identified: size ≥50 mm, patterns of distribution of hepatic nodules (single, satellites or multifocal), lymph-node metastases (N1) and R1 resections. In the VR group the 5-years OS rate in patients without lymph-node metastases undergoing R0 resection (VRR0N0) was 44.4%, while in N1 patients undergoing R1 resection was 20% (p < 0.001). Conclusion: Vascular resection (PVR and CVR) is associated with higher operative risk, but seems to be justified by the good survival results, especially in patients without other negative prognostic factors (R0N0 resections).